Oxido[N-(2-oxidobenzylidene-κO)leucinato-κ(2) N,O](1,10-phenanthroline-κ(2) N,N′)vanadium(IV) - Wang, Cheng-Yuan (International Union of Crystallography, 2012)
In the title V(IV) complex, [VO(C(13)H(15)NO(3))(C(12)H(8)N(2))], the oxidovanadium cation is N,N′-chelated by a 1-10-phenanthroline ligand and N,O,O′-chelated by a Schiff base anion in a distorted octahedral geometry. Weak intermolecular C—H⋯O hydrogen bonds occur in the crystal structure which contains solvent-accessible voids of 81 Å(3).